Solve the system by the elimination method. Check your work. x - 3y = 0 3y - 6 = 2x
x - 3y=0 3y - 6 =2x __________ x - 3y=0 ........(1) -2x + 3y=6 ........(2) __________ -x = 6 ==》x = -6 .........(3) subst. in (2) -2 (-6) + 3y = 6 ==》3y= -6 ==》y = -2
Answer:(-6,-2) Explanation: The elimination method calls for two variables that cancel each other out. In this circumstance, you already have 3y and -3y. First, make the orders of the equations the same. I got the x's to the same side on each equation. This left me with: x=3y 2x=3y-6. Now, subtract the first equation from the second one to get x=-6. That's the first part of the solution. For the y, you can just plug x into one of the equations and solve. I'll use the first one. -6-3y=0. Now get the ys to one side: -6=3y. Divide both sides by 3 to get y= -2. Now that you have an x and a y coordinate, your solution is (-6,-2). To check: plug both values in for their variables into each equation. 3(-2)-6=2(-6) solve to get... -12=-12, which is true, meaning the solution works for that equation. -6-3(-2)=0 solve to get... 0=0. The solution works for both equations.